Position paper on olfactory dysfunction: 2023 - Whitcroft, K L; Altundag, A; Balungwe, P; Boscolo-Rizzo, P; Douglas, R; Enecilla, M L B; Fjaeldstad, A W; Fornazieri, M A; Frasnelli, J; Gane, S; Gudziol, H; Gupta, N; et al. (Rhinology, 2023)
BACKGROUND: Since publication of the original Position Paper on Olfactory Dysfunction in 2017 (PPOD-17), the personal and societal burden of olfactory disorders has come sharply into focus through the lens of the COVID-19 pandemic. Clinicians, scientists and the public are now more aware of the importance of olfaction, and the impact of its dysfunction on quality of life, nutrition, social relationships and mental health. Accordingly, new basic, translational and clinical research has resulted in significant progress since the PPOD-17. In this updated document, we present and discuss currently available evidence for the diagnosis and management of olfactory dysfunction. Major updates to the current version include, amongst others: new recommendations on olfactory related terminology; new imaging recommendations; new sections on qualitative OD and COVID-19 OD; updated management section. Recommendations were agreed by all co-authors using a modified Delphi process. CONCLUSIONS: We have provided an overview of current evidence and expert-agreed recommendations for the definition, investigation, and management of OD. As for our original Position Paper, we hope that this updated document will encourage clinicians and researchers to adopt a common language, and in so doing, increase the methodological quality, consistency, and generalisability of work in this field.
Keywords: pandemie; Smell; Olfaction Disorders; kvalita života; lidé; poruchy čichu; Pandemics; Quality of Life; čich; COVID-19; Humans